Stress in nursing students: an Indonesian pilot case study - Ritonga, Imelda L.; Manurung, Sarida S.; Tan, Hedy (International Journal of Research in Medical Sciences, 2017)
Background: Previous studies have found that severe stress can occur in nursing students because of their education system; however there have not been any studies to address stress in nursing students, conducted in Indonesian. Based on the researchers’ prior observation in a private nursing school, experiencing stress may influence the students’ learning process and may also become an obstacle for them to study well. Many studies have identified that nursing education is a stressful educational process. Sources of stress in nursing students’ have been the focus of several studies, with some studies also investigating the implications of the stress on a range of factors including: academic performance, work performance; emotional ill health and psychosomatic disorders; attrition; and suicide risk. The studies reinforce that stress in nursing students, is an important factor for nursing lecturers to consider in nursing education. Students felt helpless when they could not change situations they did not like and complained that the learning approach was authoritarian. They felt they were treated more like children than adult learners but did not voice their opinions because of perceived sanctions and thus they were passive and acquiescence to college authority. The main objective is to study identified stressors in nursing students and effect of stress in the students’ learning process. Methods: A case study was used with cognitive appraisal theory from Lazarus and Folkman (1984), as the theoretical proposition. Data was collected by utilizing in-depth interviews with nursing students. Results: There were five evident themes found in this study related to stress and its effect on the students’ learning process. These themes were: (1) dormitory living (2) learning in the school (3) learning in the clinical setting (4) personal and social beliefs and (5) short-term and long-term effects. Conclusions: Results indicated that education process used in this particular school of nursing, created stress which impacted adversely on the students’ learning process. Some of the problems identified are specific to nursing education in Indonesian.